Exploring Factors Associated with Self-Management Compliance among Rural Elders with Diabetes - Ruoyan Lu M.S; Yueping Li M.P.H; Zhenquan Zheng B.S; Zi Yan Ph.D., M.P.H (SAGE Publishing, 2021)
The purpose of the study was to examine the social-ecological factors associated with diabetic self-management compliance among elders with diabetes in China. A total of 2,586 rural elderly residents who were 60-years-old or above participated in the survey. Socio-demographic factors, social support, healthcare accessibility and health risk factors were measured, along with self-reported medication and blood glucose monitoring data. Among the 117 individuals with diabetes, the medication compliance rate was 79.49%. The elderly who had high economic status were more likely to meet medication treatment compliance. Only 58.97% of study participants monitored blood glucose once a month. Younger age (<70-year-old), higher economic status, more social support and better healthcare accessibility were associated with higher blood glucose monitoring compliance odds. Diabetic medication and blood glucose testing tools should be more comprehensively covered by the national insurance program. Healthcare accessibility should be increased through transportation support, building more local facilities, such as mobile labs, and promoting affordable home-visit care. Self-management education programs about diabetes for rural elders should be promoted.